CRITICAL FACTORS OF CLOUD ACCOUNTING ACCEPTANCE AND SECURITY FOR PROSPECTIVE ACCOUNTANTS: TAM EXTENSION - Ayatulloh Michael Musyaffi; Arinal Muna (JRAK, 2021)
Cloud computing technology can change the business structure, including accounting, through cloud computing. However, cloud accounting has problems, especially those related to data, which affect user acceptance of cloud accounting. Based on these problems, this research aims to test the acceptance of cloud accounting. The object of this research focuses on cloud accounting users to prospective accountants who are still at the undergraduate degree, with a total of 123 respondents. The questionnaire was distributed via google form and then analyzed using PLS using data processing through SmartPLS. The findings of this study indicate that perceived ease of use and security can influence the intention to using cloud accounting. Meanwhile, perceived usefulness not able to control the choice to use cloud accounting. This is because prospective accountants still consider cloud as a learning medium to not guarantee uncertainty in using cloud accounting.